Pengaruh air rebusan daun pandan wangi terhadap penurunan kadar kolesterol pada mencit jantan yang di induksi propiltiourasil - SUWAIBAH SUWAIBAH (Universitas Islam Madura, 2021)
Hypercholesterolemia, which is a condition in which cholesterol levels in the blood rise above normal limits. This is shown in a study conducted in Semarang in 2007-2008, blood cholesterol levels >200 mg/dl increased the risk of heart and blood vessel disease by 1.8 times greater than blood cholesterol <200 mg/dl. Treatment using efficacious plants has already been applied from modern medicines. Fragrant pandan leaves have been used for the treatment of various diseases. The purpose of this study was to test whether the boiled water of fragrant pandan leaves can reduce the total cholesterol level of male mice used as test animals., PTU was induced. For positive control, simvastatin 10 mg was used, which is a drug to lower cholesterol levels in the blood. Male mice were divided into 4 groups consisting of Group A as normal control, Group B, C, and D were given PTU at a dose of 1.04 g with 0.5 mg, then group D (test control) was given boiled water with fragrant pandan leaves with dose of 10 ml. Group C (positive control) was given Simvastatin 10 mg at a dose of 0.16 g. The results showed that the total cholesterol levels in mice that were given boiled water from fragrant pandan leaves could reduce cholesterol levels by 11.8% mg/dl. While the administration of simvastatin showed a decrease in total cholesterol levels by 11.3% mg/dl. Cholesterol levels were measured by taking a blood sample from the tip of the tail using a syringe and then measured using a Nesco multicheck tool with a cholesterol check strip.